Epidemiology of HIV-associated peripheral neuropathy in people living with human immunodeficiency virus infection in Greece. (October 2022) - Nikolaidis, Ioannis; Karakasi, Maria-Valeria; Bakirtzis, Christos; Skoura, Lemonia; Pilalas, Dimitrios; Boziki, Marina-Kleopatra; Tsachouridou, Olga; Voultsos, Polychronis; Nikolaidis, Pavlos; Gargalianos-Kakoliris, Panagiotis; Daniilidis, Michail; Grigoriadis, Nikolaos; et al.
Background: Peripheral neuropathy is among the most common complications among people with HIV with prevalence rates varying widely among studies (10–58%). Objective: This study aims to assess the prevalence of HIV-associated peripheral neuropathy among HIV-positive people in Northern Greece monitored during the last 5-year period and investigate possible correlations with antiretroviral therapy, disease staging, and potential risk factors, as there is no prior epidemiological record in Greek patients. Methods: Four hundred twenty patients were divided into a group with peripheral neuropathy ( n = 269), and those without ( n = 151). Peripheral neuropathy was assessed with a validated Peripheral Neuropathy Screening tool. Statistical analyses were performed with SPSS, were two-tailed, and p -value was set at 0.05. Results: The incidence of peripheral neuropathy was estimated at 35.9%. Age was found to correlate with higher odds of developing HIV-peripheral neuropathy, rising by 4%/year. Females encountered 77% higher probability to develop peripheral neuropathy. Stage 3 of the disease associated with higher occurrence of peripheral neuropathy (96% as compared to stage-1 patients). Among patients with peripheral neuropathy, the duration of antiretroviral therapy was found to be longer than in those without. Conclusions: Peripheral neuropathy remains one of the most common complications regardless of the antiretroviral-therapy type, indicating the involvement of other risk factors in its occurrence, such as the stage of the disease, age and gender. Therefore, the treating physician should screen patients as early and frequently as possible upon HIV-diagnosis to prevent the progression of this debilitating condition so that prolonged life-expectancy is accompanied by a good quality of life.